APLIKASI KAFALAH PADA ASURANSI TAKAFUL PERSPEKTIF AKAD BISNIS ISLAM - Mugiyati . (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2012)
Kafalah is a kind of tabarru’ agreement which is based on the value of social virtue. Kafalah can be developed and applied on takaful insurance based on the three payment patterns of takaful. The first: participant dies during the coverage period. In this case, a kind of kafalah that can be applied is Kafalah bi al-dayn. It is the debt obligations that are being the responsibility of others. For participant who dies in the coverage period is being covered (makful 'anhu). While, the other participants are together as kafil (guarantor) to pay off the debt of makful 'anhu in the form of unpaid premium remains as makful bih. On the other hands, the receiver of guarantee (makful lahu) is the takaful insurance company. The second: the condition where participant is still alive until the time of completing the coverage period. So that, the kafalah application can be done by ta'liq (kafalah al-mu’allaqah). It is a form of kafalah where the execution of the guarantee made by a person against another person is required or suspended for a certain thing. In this position, he serves as kafil who guarantees the other participants (makful 'anhu) if they are in an accident or die. To pay the remaining premiums is to be the responsibility of makful bih through tabarru’ funds' that have been collected to insurance companies as receiver of the guarantee (makful lahu). The third: participant resigned before the contract coverage period is completed. In this circumstance, the kafalah contract has expired or has been canceled since it is a kind of tabarru’ agreement that its original legal status is not absolutely binding.